The President's shadow - Meltzer, Brad (Meltzer, Brad. Culper ring, 2015)
"Following The Inner Circle and The Fifth Assassin, Brad Meltzer returns with the next novel in the #1 New York Times bestselling Culper Ring series. Beecher White makes an alarming discovery on the White House grounds: there is a severed arm buried in the Rose Garden. As he investigates, he realizes it's a message one that may have dire repercussions for the President. Even worse, the message turns Beecher's personal life upside down, pointing him towards the dark truth about his father's death"--